Reducing Youth Vaping: A Pilot Test of the Peer-Led “Youth Engaged Strategies for Changing Adolescent Norms!” (YES-CAN!) Program - Asdigian, Nancy L.; Riggs, Nathanial R.; Valverde, Patricia A.; Crane, Lori A. (Health promotion practice, 2023)
Effective prevention interventions are needed to stem the rising tide of nicotine vaping among adolescents. We conducted a quasi-experimental, non-equivalent comparison group pilot study of the effectiveness of the “Youth Engaged Strategies for Changing Adolescent Norms” (YES-CAN!) program for reducing risks for youth nicotine vaping. YES-CAN! is an innovative peer-led program that supports older adolescents in developing and delivering short narrative prevention videos and related prevention education to younger adolescents. High-school and middle-school program participants and non-program comparison group students completed pre and post surveys assessing vaping susceptibility, behavioral intentions, resistance, knowledge, attitudes, perceived harm, and normative beliefs. Vaping knowledge and the perceived number of friends and classmates who vape showed significantly greater pre- to post-program increases among high-school participants compared to non-participants, and positive vaping attitudes demonstrated significantly greater decreases. Among middle-school students, vaping knowledge increased significantly more among program participants compared to non-participants. The findings from this study indicate that the YES-CAN! program holds promise for reducing risks of nicotine vaping among adolescents. This contributes to a growing body of evidence regarding the utility of peer-led approaches to adolescent health promotion. Further evaluation of the YES-CAN! program in a large-scale randomized control trial is warranted to determine its effectiveness in curbing the escalation of youth nicotine vaping that has characterized the past decade. Future studies should monitor program effect on perceptions of vaping prevalence to ensure participation and/or exposure does not inadvertently promote vaping by increasing perceptions that others vape.